El financiamiento de proyectos inmobiliarios de interés social a través del mercado de valores ecuatoriano - Jiménez Cabrera, Jackson (2017)
In recent decades the real estate and construction sector have been presented as one of the most dynamic sectors in the national economy. One of the main factors that generated this dynamism has been the financing of real estate projects through traditional financial markets. However, no one can deny that disadvantages and limitations on those faced by the real estate sector in particular social interest among them are still present, the short term for repayment of loans and financing costs of projects, soit is necessary to look for different sources of financing and investment including the stock market. The stock market financial resources channeled towards productive activities, through the buying and selling of securities documents and off-exchange trading mainly in the medium and long term areas. For this reason, the stock market is an alternative to the real sector of the economy under more favorable conditions that offers the traditional financial sector.